Particular history of hormonal therapies of menopause: a lived experience - Campodonico-Garibaldi, Ítalo (2019)
The history of menopausal hormone therapies (THM) begins during the 1940s when the benefits of estrogen on the climacteric syndrome were recognized. Since then the THM have suffered permanent ups and downs alternating periods of great euphoria with periods of deep depression. After more than thirty years of prescription of non-opposite estrogens, a significant increased risk of cancer and endometrial hyperplasias was demonstrated. Estrogenoterapia was proscribed! A short walk proved that the addition of progestins offered effective protection, avoiding the risks of hyperplasia and endometrial cancer. Towards the end of the 20th century, the use of THM reaches its peak, with additional benefits attributed to the cardiovascular system, memory and cognitive processes, skin and skin and quality of life. The results of the WHI study, published in 2002, all went astray, pointing to a significant increase in the risks of coronary heart disease, stroke, venous embolism and breast cancer. As a consequence, the THM totally execrated. However, the reanalysis of the data showed, in women under 60 years of age, favorable effects of THM on coronary heart disease risk. More recent studies indicate that transdermally administered estrogens associated with non-MPA progestins do not increase the risks of stroke, venous thromboembolism and breast cancer; and, they have a strong impact on the quality of life of the users. Again the THM would be finding an adequate channel.